Key Concepts and Research Methods to Analyze TikTok Journalism - Vázquez-Herrero Jorge; Negreira-Rey María-Cruz; Klug Daniel (Cultural Science)
In this paper, we propose a mixed methodological approach to frame journalism research on the emerging platform TikTok. We define the parameters and objects of study that can be analyzed in the framework of TikTok journalism and adapt the most commonly used methods in social media research, designing qualitative and quantitative methods to build mixed methodologies that are necessary to address complex objects of study. We present a phased method for data collection, a multidimensional analysis of content and messages on TikTok, and the implementation of user studies, qualitative interviews and surveys. Finally, we propose a framework for the development of future lines of research in TikTok journalism, from the perspectives of content, audiences, technology and platform, and business and strategy. All this occurs at an early stage in which TikTok journalism is dealing with adaptation to trends, social media logic and journalism values.